Vulnerability assessment of buildings in Ranau township : methodological design - Izni Izzati Mohamad; Mohd Zulkifli Mohd Yunus; Noor Sheena Herayani Harith; Lestuzzic, Pierino (Penerbit Universiti Kebangsaan Malaysia, 2019)
Structural damage usually happens during earthquake events. This had caused damage of properties and even worse, loss of lives. Usually, the greatest losses were not caused by the quake specifically, but rather because of the fall of the structures. The vulnerability is a degree which buildings are exposed to harmful and destruction and in this case, it’s to earthquake incident. The fast development in urbanization prompt higher hazard from earthquake occurrences; including in the area with intermediate earthquake activities city like this city. This study addresses the expeditious assessment of a great number of buildings in Ranau Township involving measures to identify hazards, evaluate building stocks and calculate vulnerability using a scoring method, FEMA 154 form. The selected area was selected based on building data from the local municipality. Two types of buildings were assessed; commercial buildings and residential buildings. The basic structural score was determined based on building types. Modifier score is a major factor that gives impacts to structural performance during earthquake. These two types of scores will determine the final score of the building and its vulnerability. The outcome of the study reveals a different vulnerability level where early precaution and modification are needed because of the high vulnerability risk. This method can be applied for further analysis in other seismic-prone areas.